Catalyst for preparing low-carbon olefin from synthesis gas as well as preparation method and application of catalyst

By using a catalyst containing multiple elements, the problems of low carbon monoxide conversion and low selectivity in the process of syngas-based low-carbon olefins in the prior art are solved, and efficient catalytic performance is achieved.

CN119701991AActive Publication Date: 2025-03-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311271196.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

In the process of syngas-made low-carbon olefins, the existing iron-based catalysts have low carbon monoxide conversion and low selectivity of low-carbon olefins.

Method used

A catalyst with high activity is used to form a catalyst containing iron, manganese, germanium, zirconium, D elements (such as zinc, cobalt, nickel) and alkali metal elements through a specific molar ratio and oxidation state. The catalyst shows characteristic peaks in the XPS map, indicating that the iron element is in a specific chemical environment and has good catalytic properties.

Benefits of technology

The conversion rate of reactant carbon monoxide and the selectivity of the target product low-carbon olefin are significantly improved, and the performance of the catalyst is optimized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004475608820000151
    Figure BDA0004475608820000151
  • Figure BDA0004475608820000161
    Figure BDA0004475608820000161
  • Figure HDA0004475608920000011
    Figure HDA0004475608920000011
Patent Text Reader

Abstract

The invention discloses a catalyst for preparing low-carbon olefin from synthesis gas and a preparation method and application thereof, the catalyst comprises an active component, the active component comprises an iron element, a manganese element, a germanium element, a zirconium element, a D element and an alkali metal element, and the D element is selected from at least one of zinc, cobalt and nickel. The catalyst provided by the invention is an iron-based catalyst, can solve the problem of low selectivity of low-carbon olefin in the prior art, and provides a method for directly preparing low-carbon olefin from synthesis gas, and the method has the characteristics of high conversion rate of reactant carbon monoxide and high selectivity of target product low-carbon olefin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts, and in particular relates to a catalyst for preparing light olefins from synthesis gas, and a preparation method and application thereof. Background Art

[0002] Low-carbon olefins (olefins with carbon atoms ≤ 4) represented by ethylene and propylene are the basic raw materials of the chemical industry. At present, the main raw materials of low-carbon olefins in the world are petroleum hydrocarbons, of which naphtha accounts for the majority, and there are also alkanes, hydrogenated diesel, and some heavy oils. At home and abroad, natural gas or light petroleum fractions are used as raw materials, and low-carbon olefins are produced by steam cracking process in ethylene joint units. Steam cracking is a large energy-consuming device in petrochemical industry, and it is completely dependent on non-renewable petroleum resources. With the increasing scarcity of petroleum resources, it is urgent to find alternative resources, so the research work of replacing petroleum with other resources to produce olefins has been paid attention to. Some well-known oil companies and scientific research institutes in the world have carried out research and development work in this regard. Direct preparation of low-carbon olefins from synthesis gas is one of the current research hotspots. The method of converting synthesis gas into hydrocarbons through the action of a catalyst is the process of catalytic hydrogenation of CO on a metal catalyst to produce a mixture mainly composed of straight-chain alkanes and olefins.

[0003] Iron-based catalysts are commonly used in the direct production of light olefins from syngas. Because of their good performance and economic efficiency, iron-based catalysts are currently the most commonly used catalysts for the production of light olefins from syngas. The addition of carriers and additives during the preparation process can better improve the stability and selectivity of iron-based catalysts. The prepared catalysts need to be further activated before use to improve the performance of the catalyst. With the maturity of the technology for the production of light olefins from syngas, the preparation of iron-based catalysts is also facing more challenges.

[0004] The successful preparation of iron-based catalysts is a key step in achieving good application results in the production of light olefins from syngas. The catalytic effects of iron-based catalysts prepared by different methods are also different. The selection of additives and carriers also has an important influence on the various properties of the catalyst.

[0005] However, the iron-based catalysts involved in the prior art still have the problems of low conversion rate of reactant carbon monoxide and low selectivity of target product low-carbon olefins. Summary of the invention

[0006] In order to overcome the problems existing in the prior art, the present invention provides a catalyst for preparing light olefins from synthesis gas and a preparation method thereof, wherein the catalyst is an iron-based catalyst, which can solve the problem of low selectivity of light olefins in the prior art. The method for directly preparing light olefins from synthesis gas provided by the present invention has the characteristics of high conversion rate of reactant carbon monoxide and high selectivity of target product light olefins.

[0007] One of the purposes of the present invention is to provide a catalyst for preparing light olefins from synthesis gas, which includes active components, wherein the active components include iron, manganese, germanium, zirconium, D, and alkali metal elements, and the D element is selected from at least one of zinc, cobalt, and nickel.

[0008] Preferably, each element in the active component exists in the form of oxides. More preferably, the catalyst comprises an active component, and the active component consists of iron, manganese, germanium, zirconium, D, and alkali metal elements.

[0009] In a preferred embodiment, the alkali metal is selected from at least one of lithium, sodium and potassium.

[0010] In a preferred embodiment, in the catalyst, the molar ratio of manganese element to iron element is (30-130):100, preferably (40-120):100.

[0011] For example, in the catalyst, the molar ratio of manganese element to iron element is 30:100, 50:100, 70:100, 90:100, 110:100 or 130:100.

[0012] In a preferred embodiment, in the catalyst, the molar ratio of germanium to iron is (4-30):100, preferably (4-15):100.

[0013] For example, in the catalyst, the molar ratio of germanium element to iron element is 4:100, 5:100, 10:100, 15:100, 20:100, 25:100 or 30:100.

[0014] In a preferred embodiment, in the catalyst, the molar ratio of zirconium element to iron element is (10-60):100, preferably (15-40):100.

[0015] For example, in the catalyst, the molar ratio of zirconium element to iron element is 10:100, 20:100, 30:100, 40:100, 50:100 or 60:100.

[0016] In a preferred embodiment, in the catalyst, the molar ratio of the D element to the iron element is (5-30):100, preferably (10-25):100.

[0017] For example, in the catalyst, the molar ratio of the D element to the iron element is 5:100, 10:100, 15:100, 20:100, 25:100 or 30:100.

[0018] In a preferred embodiment, in the catalyst, the molar ratio of the alkali metal element to the iron element is (1-10):100, preferably (2-8):100.

[0019] For example, in the catalyst, the molar ratio of the alkali metal element to the iron element is 1:100, 2:100, 4:100, 6:100, 8:100 or 10:100.

[0020] In a preferred embodiment, the active component comprises a composition represented by the following formula:

[0021] Fe 100 Mn a Ge b Zr c D d E e O x , wherein: the D element is selected from at least one of zinc, cobalt and nickel; the E element represents an alkali metal element; the value range of a is 30 to 130, preferably 40 to 120; the value range of b is 4 to 30, preferably 4 to 15; the value range of c is 10 to 60, preferably 15 to 40; the value range of d is 5 to 30, preferably 10 to 25; the value range of e is 1 to 10, preferably 2 to 8; x is the total number of oxygen atoms required to satisfy the valence of each element in the catalyst.

[0022] In a preferred embodiment, the XPS spectrum of the catalyst has a characteristic peak of 707.5±1.0 eV, which is attributed to the iron element.

[0023] Among them, the presence of this characteristic peak indicates that the iron atom is in a special chemical environment. The iron in this specific chemical environment, as the main component of the catalyst of the present invention, has a good effect on the adsorption and cracking of reactants in the synthesis gas to light olefin reaction, the generation of intermediates, the generation of target products and desorption, so that the catalyst performance, i.e., the carbon monoxide conversion rate and the light olefin selectivity, are very high.

[0024] In a further preferred embodiment, the XPS spectrum of the catalyst further has a characteristic peak of 721 eV±1.0 eV, which is attributed to the iron element.

[0025] In a preferred embodiment, the catalyst further contains a binder.

[0026] In a further preferred embodiment, the binder is selected from at least one of silicon dioxide, aluminum oxide and titanium dioxide.

[0027] In a further preferred embodiment, based on 100 wt % of the catalyst, the content of the binder is 2-15 wt %, for example, 2 wt %, 5 wt %, 8 wt %, 10 wt %, 12 wt % or 15 wt %.

[0028] The catalyst of the present invention has the characteristics of high conversion rate of reactant carbon monoxide and high selectivity of target product light olefins under the synergistic effect of iron, manganese, germanium, zirconium, D and alkali metal elements (preferably none of them can be missing).

[0029] The second object of the present invention is to provide a method for preparing a catalyst for preparing low-carbon olefins from synthesis gas, preferably for preparing the catalyst described in one of the objects of the present invention, the preparation method comprising: first precipitating and aging a solution containing an iron precursor and a solution containing a zirconium precursor, and then mixing with raw materials including a solution containing a manganese precursor, a solution containing a germanium precursor, a solution containing a D element precursor, and a solution containing an alkali metal element precursor, and drying (for example, spray drying) and calcining to obtain the catalyst.

[0030] In a preferred embodiment, the preparation method comprises:

[0031] (1) mixing a solution containing an iron precursor and a solution containing a zirconium precursor to obtain a dispersion I;

[0032] (2) mixing a precipitant with the dispersion I, and subjecting the mixture to precipitation and aging to obtain a dispersion II;

[0033] (3) separating the solid phase in the dispersion II, washing it, and obtaining a precipitate;

[0034] (4) The precipitate is mixed with a solution containing a manganese precursor, a solution containing a germanium precursor, a solution containing a D element precursor, and a binder, the pH is adjusted, and then a solution containing an alkali metal element precursor is added, mixed, and dried (e.g., spray dried) and calcined to obtain the catalyst.

[0035] In a preferred embodiment, the iron precursor is selected from at least one of iron nitrate, iron carbonate and iron oxalate, preferably iron nitrate.

[0036] In a preferred embodiment, the zirconium precursor is selected from at least one of zirconium nitrate, zirconium carbonate and zirconium oxalate, preferably zirconium nitrate.

[0037] In a preferred embodiment, the manganese precursor is selected from at least one of manganese nitrate, manganese carbonate and manganese oxalate, preferably manganese nitrate.

[0038] In a preferred embodiment, the germanium precursor is selected from at least one of germanium nitrate, germanium carbonate and germanium oxalate, preferably germanium nitrate.

[0039] In a preferred embodiment, the D element precursor is selected from at least one of the D element nitrate, the D element carbonate, and the D element oxalate, preferably the D element nitrate.

[0040] In a preferred embodiment, the alkali metal element precursor is selected from at least one of alkali metal nitrates, alkali metal carbonates, and alkali metal hydroxides, preferably alkali metal hydroxides.

[0041] In the present invention, the "solution" in step (1) and step (4) preferably refers to an aqueous solution.

[0042] In a preferred embodiment, the molar ratio of iron in the iron precursor to zirconium in the zirconium precursor is 100:(10-60), preferably 100:(15-40); and / or the molar ratio of iron in the iron precursor to manganese in the manganese precursor is 100:(30-130), preferably 100:(40-120); and / or the molar ratio of iron in the iron precursor to germanium in the germanium precursor is 100:(30-130), preferably 100:(40-120). The molar ratio of iron in the iron precursor to the D element in the D element precursor is 100:(4-30), preferably 100:(4-15); and / or the molar ratio of iron in the iron precursor to the alkali metal element in the alkali metal element precursor is 100:(1-10), preferably 100:(2-8).

[0043] In a preferred embodiment, the precipitant in step (2) is selected from alkaline precipitants, preferably at least one selected from ammonia water, urea, and organic amines; more preferably, the organic amine is selected from at least one selected from methylamine, ethylamine, and ethylenediamine.

[0044] In a further preferred embodiment, in step (2), the molar amount of the precipitant is greater than or equal to the sum of the molar amount of the iron element in the iron precursor, the molar amount of the zirconium element in the zirconium precursor, the molar amount of the manganese element in the manganese precursor, the molar amount of the germanium element in the germanium precursor, the molar amount of the D element in the D element precursor, and the molar amount of the alkali element in the alkali metal element precursor.

[0045] Preferably, the ratio of the precipitant to the sum of the molar amount of iron element in the iron precursor, the molar amount of zirconium element in the zirconium precursor, the molar amount of manganese element in the manganese precursor, the molar amount of germanium element in the germanium precursor, the molar amount of D element in the D element precursor, and the molar amount of alkali element in the alkali metal element precursor is 1:(1-2), preferably 1:(1-1.5), for example, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9 or 1:2.

[0046] In a preferred embodiment, in step (2), the precipitation is carried out at room temperature to 95°C, preferably at 50 to 90°C; more preferably, the temperature is kept at 0.2 to 4 hours, preferably at 0.5 to 3 hours.

[0047] For example, in step (2), the precipitation is carried out at 50°C, 60°C, 70°C, 80°C, 90°C or 95°C; and the temperature is kept for 0.2h, 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h or 4h.

[0048] In a preferred embodiment, in step (2), the aging is carried out at room temperature, preferably for 10 to 30 hours, for example, 10 hours, 12 hours, 15 hours, 18 hours, 20 hours, 22 hours, 25 hours, 28 hours or 30 hours.

[0049] In a preferred embodiment, in step (3), washing is performed with water.

[0050] In a preferred embodiment, in step (4), the binder is selected from at least one of silicon dioxide, aluminum oxide and titanium dioxide.

[0051] In a further preferred embodiment, based on the total weight of 100wt% of the iron element in the iron precursor, the zirconium element in the zirconium precursor, the manganese element in the manganese precursor, the germanium element in the germanium precursor, the D element in the D element precursor, and the alkali metal element in the alkali metal element precursor, the amount of the binder is 3 to 25wt%, for example, 3wt%, 5wt%, 10wt%, 15wt%, 20wt% or 25wt%.

[0052] In a preferred embodiment, in step (4), the pH is adjusted to 1-6, for example, 1, 2, 3, 4, 5 or 6.

[0053] In a preferred embodiment, in step (4), the calcination temperature is 300-800° C. and the calcination time is 2-12 hours.

[0054] In a further preferred embodiment, in step (4), the calcination temperature is 400-700° C. and the calcination time is 3-10 h.

[0055] In a preferred embodiment, the catalyst is subjected to reduction treatment and carbonization treatment before use.

[0056] In a preferred embodiment, the reduction treatment conditions include: a pressure of 0 to 2 MPa; and / or a catalyst load of 3000 to 6000 mL·h -1 ·g -1 ; and / or, the temperature is 200 to 550°C; and / or, the time is 12 to 48 hours; and / or, the heating rate is 1 to 15°C / minute.

[0057] For example, the pressure is 0 MPa, 0.2 MPa, 0.5 MPa, 0.8 MPa, 1 MPa, 1.2 MPa, 1.5 MPa, 1.8 MPa or 2 MPa; and / or the catalyst loading is 3000, 3500, 4000, 4500, 5000, 5500 or 6000 mL·h -1 ·g -1 ; and / or, the temperature is 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C or 550°C; and / or, the time is 12, 15, 20, 25, 30, 35, 40, 45 or 48 hours; and / or, the heating rate is 1, 2, 5, 8, 10, 12 or 15°C / minute.

[0058] In a further preferred embodiment, the atmosphere for the reduction treatment is a mixed gas containing H2 and N2; preferably, based on the total volume of the mixed gas, the volume concentration of H2 is 1% to 20%, and the volume concentration of N2 is 80% to 99%.

[0059] For example, based on the total volume of the mixed gas, the volume concentration of H2 is 1%, 2%, 5%, 8%, 10%, 12%, 15%, 18% or 20%, and the volume concentration of N2 is 82%, 85%, 88%, 90%, 92%, 95%, 98% or 99%.

[0060] In a preferred embodiment, the carbonization treatment conditions include: a pressure of 0 to 2 MPa; and / or a catalyst load of 3000 to 6000 mL·h -1 ·g -1 ; and / or, the temperature is 200 to 550°C; and / or, the time is 12 to 48 hours; and / or, the heating rate is 3 to 20°C / minute.

[0061] For example, the carbonization treatment conditions include: a pressure of 0, 0.2, 0.5, 0.8, 1, 1.2, 1.5, 1.8 or 2 MPa; and / or a catalyst load of 3000, 3500, 4000, 4500, 5000, 5500 or 6000 mL·h -1 ·g -1 ; and / or, the temperature is 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C or 550°C; and / or, the time is 12, 15, 20, 25, 30, 35, 40, 45 or 48 hours; and / or, the heating rate is 3, 5, 8, 10, 12, 15, 18 or 20°C / minute.

[0062] In a further preferred embodiment, the atmosphere for the carbonization treatment is a mixed gas containing CO and / or C2H4 and N2; preferably, based on the total volume of the mixed gas (100%), the total volume concentration of CO and / or C2H4 is 10% to 60% (for example, 10%, 20%, 30%, 40%, 50% or 60%), and the volume concentration of N2 is 40% to 90% (for example, 40%, 50%, 60%, 70%, 80% or 90%); more preferably, based on the total volume concentration of CO and C2H4 as 100%, CO is 0% to 100%, preferably 20% to 80% (for example, 20%, 40%, 60% or 80%), and C2H4 is 0% to 100%, preferably 20% to 80% (for example, 20%, 40%, 60% or 80%).

[0063] The third object of the present invention is to provide a catalyst obtained by the preparation method described in the second object of the present invention.

[0064] A fourth object of the present invention is to provide the use of the catalyst described in the first object of the present invention or the catalyst obtained by the preparation method described in the second object of the present invention in the direct preparation of light olefins from synthesis gas.

[0065] The fifth object of the present invention is to provide a method for directly preparing low-carbon olefins from synthesis gas, comprising: in the presence of a catalyst, H2 and CO are contacted and reacted, wherein the catalyst is selected from the catalyst described in one of the objects of the present invention or the catalyst obtained by the preparation method described in the second object of the present invention.

[0066] In a preferred embodiment, the catalyst is first subjected to the reduction treatment and the carbonization treatment before the contacting.

[0067] In a preferred embodiment, the reaction temperature is 200-600°C; and / or, the reaction pressure is 0.5-10 MPa; and / or, based on the amount of the pre-reduction catalyst, the volumetric space velocity of the synthesis gas is 100-8000 mL·h-1 ·g -1 ; and / or, the H2 / CO molar ratio in the synthesis gas is 0.1 to 5.

[0068] For example, the reaction temperature is 200°C, 300°C, 400°C, 500°C or 600°C; and / or, the reaction pressure is 0.5, 0.6, 0.7, 0.8, 0.9 or 10 MPa; and / or, based on the amount of the pre-reduction catalyst, the volumetric space velocity of the synthesis gas is 100, 200, 500, 800, 1000, 2000, 4000, 6000 or 8000 mL·h -1 ·g -1 ; and / or, the H2 / CO molar ratio in the synthesis gas is 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 or 5.

[0069] In a preferred embodiment, the low-carbon olefin is a C2-C4 olefin.

[0070] The endpoints and any values ​​of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values ​​should be understood to include values ​​close to these scopes or values. For numerical ranges, the endpoint values ​​of each scope, the endpoint values ​​of each scope and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be regarded as specifically disclosed in this article.

[0071] Compared with the prior art, the present invention has the following beneficial effects: the microspherical fluidized bed catalyst provided by the present invention utilizes the interaction between various additives, especially Ge, etc. and the catalyst main agent Fe, so that when the reaction of directly preparing light olefins from fluidized bed synthesis gas is carried out, the carbon monoxide conversion rate can be increased, and the content of light olefin products (C2 = +C3 = :C4 = ) ratio, which is conducive to the production of more valuable ethylene and propylene. BRIEF DESCRIPTION OF THE DRAWINGS

[0072] Figure 1 The XPS spectrum of the catalyst obtained in Example 1 is shown. DETAILED DESCRIPTION

[0073] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0074] It should also be noted that the various specific technical features described in the following specific embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0075] In addition, the various embodiments of the present invention may be arbitrarily combined as long as they do not violate the concept of the present invention. The technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.

[0076] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0077] The catalyst compositions in the examples are theoretical values ​​estimated based on the amounts of raw materials used.

[0078] [Example 1]

[0079] (1) Take 427.2 g of ferric nitrate, add 1000 g of water, stir and dissolve to obtain material I, take 157.3 g of zirconium nitrate, add 500 g of water, heat and stir until dissolved, and obtain material II.

[0080] Mix material I and material II, add 360 g of urea, heat to 90°C with stirring for precipitation reaction, and keep at 90°C for 30 minutes; after precipitation, place at room temperature for aging for 20 hours; then wash (wash with water) and separate to obtain a precipitate.

[0081] (2) 296.7 g of manganese nitrate solution, 100 ml of tetrahydroxygermanium solution containing 19.51 g, 200 ml of zinc nitrate solution containing 56.62 g, and 62.5 g of 40% (weight) silica sol material were added to the above precipitate under stirring, and then the pH value of the above slurry was adjusted with ammonia water so that the pH value of the mixed slurry was 6.0. After stirring evenly, 50 g of a solution containing 3.55 g of KOH was added to obtain a material. After being fully stirred, the prepared slurry was subjected to micro-spheroidal particle forming in a spray dryer according to the usual method, and finally a micro-spheroidal particle with an inner diameter of 89 mm and a length of 1700 mm ( mm) in a rotary calcining furnace at 500°C for 2.0 hours to prepare a catalyst composition of:

[0082] 90 wt% Fe 100 Mn 80 Ge 18 Zr 35 Zn 18 K5O x +10 wt% SiO2

[0083] The XPS spectrum of the obtained catalyst is shown in Figure 1 a, It is obvious from the figure that the displacement of iron is at 707.5 eV.

[0084] [Example 2]

[0085] (1) Take 642.6 grams of iron nitrate, add 1000 grams of water, stir and dissolve to obtain material I, take 135.2 grams of zirconium nitrate, add 500 grams of water, heat and stir until dissolved, and obtain material II.

[0086] Mix material I and material II, add 430 g of urea, heat to 90°C with stirring for precipitation reaction, and keep at 90°C for 30 minutes; after precipitation, place at room temperature for aging for 20 hours; then wash (wash with water) and separate to obtain a precipitate.

[0087] (2) 223.1 g of manganese nitrate solution, 100 ml of tetrahydroxygermanium solution containing 16.31 g, 200 ml of zinc nitrate solution containing 47.32 g, and 25.00 g of 40% (by weight) silica sol material were added to the above precipitate under stirring, and then the pH value of the above slurry was adjusted with ammonia water so that the pH value of the mixed slurry was 6.0. After stirring evenly, 50 g of a solution containing 2.13 g of KOH was added to obtain a material. After being fully stirred, the prepared slurry was subjected to micro-spheroidal particle forming in a spray dryer according to a conventional method, and finally a micro-spheroidal particle with an inner diameter of 89 mm and a length of 1700 mm ( mm) in a rotary calcining furnace at 500°C for 2.0 hours to prepare a catalyst composition of:

[0088] 96 wt% Fe 100 Mn 40 Ge 10 Zr 20 Zn 10 K2O x +4 wt% SiO2

[0089] The XPS spectrum of the obtained catalyst showed that the iron shift was at 708.2 eV.

[0090] [Example 3]

[0091] (1) Take 323.9 grams of iron nitrate, add 1000 grams of water, stir and dissolve to obtain material I, take 170.3 grams of zirconium nitrate, add 500 grams of water, heat and stir until dissolved, and obtain material II.

[0092] Mix material I and material II, add 330 g of urea, heat to 90°C with stirring for precipitation reaction, and keep at 90°C for 30 minutes; after precipitation, place at room temperature for aging for 20 hours; then wash (wash with water) and separate to obtain a precipitate.

[0093] (2) 337.4 g of manganese nitrate solution, 100 ml of tetrahydroxygermanium solution containing 20.54 g, 200 ml of zinc nitrate solution containing 59.62 g, and 81.25 g of 40% (by weight) silica sol material were added to the above precipitate under stirring, and then the pH value of the above slurry was adjusted with ammonia water so that the pH value of the mixed slurry was 6.0. After stirring evenly, 50 g of a solution containing 4.30 g of KOH was added to obtain a material. After being fully stirred, the prepared slurry was subjected to micro-spheroidal particle forming in a spray dryer according to a conventional method, and finally a micro-spheroidal particle with an inner diameter of 89 mm and a length of 1700 mm ( mm) in a rotary calcining furnace at 500°C for 2.0 hours to prepare a catalyst composition of:

[0094] 87 wt% Fe 100 Mn 120 Ge 25 Zr 50 Zn 25 K8O x +13 wt% SiO2

[0095] The XPS spectrum of the obtained catalyst showed that the iron shift was at 707.1 eV.

[0096] [Example 4]

[0097] (1) Take 431.5 g of ferric nitrate, add 1000 g of water, stir and dissolve to obtain material I, take 158.8 g of zirconium nitrate, add 500 g of water, heat and stir until dissolved, and obtain material II.

[0098] Mix material I and material II, add 360 g of urea, heat to 90°C with stirring for precipitation reaction, and keep at 90°C for 30 minutes; after precipitation, place at room temperature for aging for 20 hours; then wash (wash with water) and separate to obtain a precipitate.

[0099] (2) 299.6 g of manganese nitrate solution, 100 ml of tetrahydroxygermanium solution containing 19.71 g, 100 ml of zinc nitrate solution containing 28.59 g, 100 ml of cobalt nitrate solution containing 27.70 g, and 62.5 g of 40% (by weight) silica sol material were added to the above precipitate under stirring, and then the pH value of the above slurry was adjusted with ammonia water so that the pH value of the mixed slurry was 6.0. After stirring evenly, 50 g of a solution containing 3.58 g of KOH was added to obtain a material. After being fully stirred, the prepared slurry was subjected to micro-spheroidal molding in a spray dryer according to a conventional method, and finally a micro-spheroidal molding machine with an inner diameter of 89 mm and a length of 1700 mm ( mm) in a rotary calcining furnace at 500°C for 2.0 hours to prepare a catalyst composition of:

[0100] 90 wt% Fe 100 Mn 80 Ge18 Zr 35 Zn9Co9K5O x +10 wt% SiO2

[0101] The XPS spectrum of the obtained catalyst showed that the iron shift was at 706.8 eV.

[0102] [Example 5]

[0103] (1) Take 431.0 g of ferric nitrate, add 1000 g of water, stir and dissolve to obtain material I, take 158.6 g of zirconium nitrate, add 500 g of water, heat and stir until dissolved, and obtain material II.

[0104] Mix material I and material II, add 370 g of urea, heat to 90°C with stirring for precipitation reaction, and keep at 90°C for 30 minutes; after precipitation is completed, place at room temperature for aging for 20 hours; then wash (wash with water) and separate to obtain a precipitate.

[0105] (2) 299.3 g of manganese nitrate solution, 100 ml of tetrahydroxygermanium solution containing 19.68 g, 200 ml of zinc nitrate solution containing 57.12 g, and 62.5 g of 40% (weight) silica sol material were added to the above precipitate under stirring, and then the pH value of the above slurry was adjusted with ammonia water so that the pH value of the mixed slurry was 6.0. After stirring evenly, 50 g of a solution containing 2.15 g of KOH and 0.80 g of NaOH was added to obtain a material. After being fully stirred, the prepared slurry was subjected to micro-spheroidal particle forming in a spray dryer according to a conventional method, and finally a micro-spheroidal particle with an inner diameter of 89 mm and a length of 1700 mm ( mm) in a rotary calcining furnace at 500°C for 2.0 hours to prepare a catalyst composition of:

[0106] 90 wt% Fe 100 Mn 80 Ge 18 Zr 35 Zn 18 K3Na2O x +10 wt% SiO2

[0107] The XPS spectrum of the obtained catalyst showed that the iron shift was at 707.1 eV.

[0108] [Comparative Example 1]

[0109] (1) Take 427.2 g of ferric nitrate, add 1000 g of water, stir and dissolve to obtain material I, take 157.3 g of zirconium nitrate, add 500 g of water, heat and stir until dissolved, and obtain material II.

[0110] Mix material I and material II, add 360 g of urea, heat to 90°C with stirring to carry out precipitation reaction, and keep at 90°C for 30 minutes.

[0111] (2) 296.7 g of manganese nitrate solution, 100 ml of tetrahydroxygermanium solution containing 19.51 g, 200 ml of zinc nitrate solution containing 56.62 g, and 62.5 g of 40% (weight) silica sol material were added to the above materials under stirring, and then the pH value of the above slurry was adjusted with ammonia water so that the pH value of the mixed slurry was 6.0. After stirring evenly, 50 g of a solution containing 3.55 g of KOH was added to obtain a material. After being fully stirred, the prepared slurry was subjected to micro-spheroidal particle forming in a spray dryer according to a conventional method, and finally a micro-spheroidal particle with an inner diameter of 89 mm and a length of 1700 mm ( mm) in a rotary calcination furnace at 500°C for 2.0 hours to prepare a catalyst.

[0112] The XPS spectrum of the obtained catalyst is shown in Figure 1 b. It can be clearly seen from the figure that the displacement of iron is at 710.1 eV.

[0113] [Comparative Example 2]

[0114] The process of Example 1 was repeated, except that the tetrahydroxygermanium solution was not used in step (2).

[0115] (1) Take 427.2 g of ferric nitrate, add 1000 g of water, stir and dissolve to obtain material I, take 157.3 g of zirconium nitrate, add 500 g of water, heat and stir until dissolved, and obtain material II.

[0116] Mix material I and material II, add 360 g of urea, heat to 90°C with stirring for precipitation reaction, and keep at 90°C for 30 minutes; after precipitation, place at room temperature for aging for 20 hours; then wash (wash with water) and separate to obtain a precipitate.

[0117] (2) 296.7 g of manganese nitrate solution, 200 ml of zinc nitrate solution containing 56.62 g, and 62.5 g of 40% (by weight) silica sol material were added to the above precipitate under stirring, and then the pH value of the above slurry was adjusted with ammonia water so that the pH value of the mixed slurry was 6.0. After stirring evenly, 50 g of a solution containing 3.55 g of KOH was added to obtain a material. After sufficient stirring, the prepared slurry was subjected to micro-spheroidal particle forming in a spray dryer according to the conventional method, and finally a micro-spheroidal particle with an inner diameter of 89 mm and a length of 1700 mm ( mm) in a rotary calcination furnace at 500°C for 2.0 hours to prepare a catalyst.

[0118] The XPS spectrum of the obtained catalyst showed that the iron shift was at 705.2 eV.

[0119] [Comparative Example 3]

[0120] (1) Take 427.2 g of ferric nitrate, add 1000 g of water, stir and dissolve to obtain material I.

[0121] 360 g of urea was added to material I, and the mixture was heated to 90°C with stirring for precipitation reaction, and maintained at 90°C for 30 minutes. After the precipitation was completed, the mixture was aged at room temperature for 20 hours. The precipitate was then washed and separated.

[0122] (2) 296.7 g of manganese nitrate solution, 100 ml of tetrahydroxygermanium solution containing 19.51 g, 200 ml of zinc nitrate solution containing 56.62 g, and 62.5 g of 40% (weight) silica sol material were added to the above precipitate under stirring, and then the pH value of the above slurry was adjusted with ammonia water so that the pH value of the mixed slurry was 6.0. After stirring evenly, 50 g of a solution containing 3.55 g of KOH was added to obtain a material. After being fully stirred, the prepared slurry was subjected to micro-spheroidal particle forming in a spray dryer according to the usual method, and finally a micro-spheroidal particle with an inner diameter of 89 mm and a length of 1700 mm ( mm) in a rotary calcination furnace at 500°C for 2.0 hours to prepare a catalyst.

[0123] The XPS spectrum of the obtained catalyst showed that the iron shift was at 707.5 eV.

[0124] [Comparative Example 4]

[0125] The process of Example 1 was repeated, except that zinc nitrate solution was not used in step (2).

[0126] (1) Take 427.2 grams of iron nitrate, add 1000 grams of water, stir and dissolve to obtain material I, take 157.3 grams of zirconium nitrate, add 500 grams of water, heat and stir to dissolve, and obtain material II.

[0127] Mix material I and material II, add 360 g of urea, heat to 90°C with stirring for precipitation reaction, and keep at 90°C for 30 minutes; after precipitation, place at room temperature for aging for 20 hours; then wash (wash with water) and separate to obtain a precipitate.

[0128] (2) 296.7 g of manganese nitrate solution, 100 ml of tetrahydroxygermanium solution containing 19.51 g, and 62.5 g of 40% (weight) silica sol material were added to the above precipitate under stirring, and then the pH value of the above slurry was adjusted with ammonia water so that the pH value of the mixed slurry was 6.0. After stirring evenly, 50 g of a solution containing 3.55 g of KOH was added to obtain a material. After sufficient stirring, the prepared slurry was subjected to micro-spheroidal particle forming in a spray dryer according to the conventional method, and finally a micro-spheroidal particle with an inner diameter of 89 mm and a length of 1700 mm ( mm) in a rotary calcination furnace at 500°C for 2.0 hours to prepare a catalyst.

[0129] The XPS spectrum of the obtained catalyst showed that the iron shift was at 709.2 eV.

[0130] [Experimental Example] Direct preparation of light olefins from syngas

[0131] The catalysts prepared in the examples and comparative examples were used to synthesize low-carbon olefins under the following conditions:

[0132] (1) The obtained catalyst was reduced by heating the mixture to 300°C at a rate of 3°C / min using 5% by volume H2 / 95% by volume N2 gas; the mixture was heated to 300°C at a pressure of 1.0 MPa, a catalyst loading of 100 g, and a catalyst load of 4000 mL·h -1 ·g -1 , 300℃ for 15 hours.

[0133] (2) The catalyst was carbonized by heating the mixture of 20 vol% C2H4 and CO (30 vol% C2H4, 70 vol% CO) / 80 vol% N2 gas at 5°C / min to 350°C at a pressure of 1.0 MPa, a catalyst loading of 100 g, and a catalyst load of 4000 mL·h -1 ·g -1 , 350℃ for 20 hours.

[0134] (3) The reaction for preparing light olefins is carried out under the following conditions:

[0135] Millimeter Fluidized Bed Reactor

[0136] Reaction temperature 330℃

[0137] Reaction pressure 2.0MPa

[0138] The catalyst loading is equivalent to 100 grams of catalyst before reduction

[0139] The catalyst loading was based on the amount of catalyst before reduction, 4000 mL·h -1 ·g -1

[0140] Raw material ratio (molar) H2 / CO=3 / 1.

[0141] The experimental results are shown in the following table:

[0142] Table 1

[0143]

[0144]

[0145] It can be seen from the above table that the catalysts in each embodiment have excellent performance: the CO conversion rate is greater than 90%, and the product (C2= +C3 = ):C4 = Greater than 4.0, far superior to the corresponding values ​​of the comparative examples.

[0146] The product (C2 = +C3 = ):C4 = The higher the ratio, the better. The higher the ratio, the higher the content of ethylene (C2 = ), propylene (C3 = ) content is high, butene (C4 = ) content is low, while the market demand for ethylene and propylene is far greater than the demand for butene.

[0147] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

Claims

1. A catalyst for preparing light olefins from synthesis gas, comprising active components, wherein the active components include iron, manganese, germanium, zirconium, D, and alkali metal elements, and the D element is selected from at least one of zinc, cobalt, and nickel.

2. The catalyst according to claim 1, characterized in that The alkali metal is selected from at least one of lithium, sodium and potassium.

3. The catalyst according to claim 1, characterized in that In the catalyst: The molar ratio of manganese to iron is (30-130):100, preferably (40-120):100; and / or, The molar ratio of germanium to iron is (4-30):100, preferably (4-15):100; and / or, The molar ratio of zirconium to iron is (10-60):100, preferably (15-40):100; and / or, The molar ratio of the D element to the iron element is (5-30):100, preferably (10-25):100; and / or, The molar ratio of the alkali metal element to the iron element is (1-10):100, preferably (2-8):

100.

4. The catalyst according to any one of claims 1 to 3, characterized in that The catalyst further contains a binder; preferably, the binder is selected from at least one of silicon dioxide, aluminum oxide and titanium dioxide; more preferably, based on 100 wt % of the catalyst, the content of the binder is 2 to 15 wt %.

5. A method for preparing a catalyst for preparing light olefins from synthesis gas, preferably for preparing the catalyst according to any one of claims 1 to 4, the preparation method comprising: The solution containing an iron precursor and a solution containing a zirconium precursor are first precipitated and aged, and then mixed with raw materials including a solution containing a manganese precursor, a solution containing a germanium precursor, a solution containing a D element precursor, and a solution containing an alkali metal element precursor, and then dried and calcined to obtain the catalyst.

6. The preparation method according to claim 5, characterized in that: The iron precursor is selected from at least one of iron nitrates, iron carbonates, and iron oxalates; and / or the zirconium precursor is selected from at least one of zirconium nitrates, zirconium carbonates, and zirconium oxalates; and / or the manganese precursor is selected from at least one of manganese nitrates, manganese carbonates, and manganese oxalates; and / or the germanium precursor is selected from at least one of germanium nitrates, germanium carbonates, and germanium oxalates; and / or the D element precursor is selected from at least one of D element nitrates, D element carbonates, and D element oxalates; and / or the alkali metal element precursor is selected from at least one of alkali metal nitrates, alkali metal carbonates, and alkali metal hydroxides.

7. The preparation method according to claim 5, characterized in that: The molar ratio of iron in the iron precursor to zirconium in the zirconium precursor is 100:(10-60), preferably 100:(15-40); and / or the molar ratio of iron in the iron precursor to manganese in the manganese precursor is 100:(30-130), preferably 100:(40-120); and / or the molar ratio of iron in the iron precursor to germanium in the germanium precursor is 100:(40-120). :(4~30), preferably 100:(4~15); and / or, the molar ratio of iron in the iron precursor to the D element in the D element precursor is 100:(5~30), preferably 100:(10~25); and / or, the molar ratio of iron in the iron precursor to the alkali metal element in the alkali metal element precursor is 100:(1~10), preferably 100:(2~8).

8. The preparation method according to any one of claims 5 to 7, characterized in that: The preparation method comprises: (1) mixing a solution containing an iron precursor and a solution containing a zirconium precursor to obtain a dispersion I; (2) mixing a precipitant with the dispersion I, and obtaining a dispersion II through precipitation and aging; (3) separating a solid phase in the dispersion II, washing, and obtaining a precipitate; (4) mixing the precipitate with a solution containing a manganese precursor, a solution containing a germanium precursor, a solution containing a D element precursor, and a binder, adjusting the pH, and then adding a solution containing an alkali metal element precursor, mixing, and obtaining the catalyst through drying and calcining.

9. The preparation method according to claim 8, characterized in that: The precipitant in step (2) is selected from alkaline precipitants, preferably at least one selected from ammonia water, urea, and organic amines; and / or, In step (4), the binder is selected from at least one of silicon dioxide, aluminum oxide and titanium dioxide; and / or, In step (4), adjusting the pH to 1-6; and / or, In step (4), the calcination temperature is 300 to 800° C. and the calcination time is 2 to 12 hours.

10. A catalyst obtained by the preparation method according to any one of claims 5 to 9.

11. Use of the catalyst according to any one of claims 1 to 4 or the catalyst obtained by the preparation method according to any one of claims 5 to 9 in the direct preparation of light olefins from synthesis gas.

12. A method for directly preparing light olefins from synthesis gas, comprising: In the presence of a catalyst, H2 and CO are contacted to react, wherein the catalyst is selected from the catalyst described in one of claims 1 to 4 or a catalyst obtained by the preparation method described in one of claims 5 to 9; preferably, the catalyst is subjected to reduction treatment and carbonization treatment before the contact.

13. The method according to claim 12, characterized in that The reaction temperature is 200-600°C; and / or, the reaction pressure is 0.5-10 MPa; and / or, based on the amount of the catalyst before reduction, the volume space velocity of the synthesis gas is 100-8000 mL·h -1 ·g -1 ; and / or, the H2 / CO molar ratio in the synthesis gas is 0.1 to 5.

Citation Information

Patent Citations

  • Method for directly preparing low-carbon alpha-olefins from synthetic gas, and preparation method thereof

    CN110575833A

  • Catalyst for producing low-carbon olefin by Fischer-Tropsch synthesis, and applications thereof

    CN111068740A

  • Catalyst for preparing low-carbon olefin from synthesis gas as well as preparation method and application of catalyst

    CN112642435A

  • Catalyst for preparing low-carbon olefin from synthesis gas as well as preparation method and application of catalyst

    CN112705218A

  • Controlling the ratio of ethylene to propylene produced in an oxygenate to olefin conversion process

    SG121577A1